Self-Efficacy and Emotional Intelligence as Predictors of Public Speaking Anxiety in College Students - Mariati, Sri; Prasetya , Berta Esti Ari (CV. Publikasi Indonesia, 2025)
This study involved three variables, namely self-efficacy (X1), emotional intelligence (X2), and anxiety of public speaking (Y). The research sample consists of 175 students from the class of 2017 (semester 2) at Satya Wacana Christian University (Universitas Kristen Satya Wacana, UKSW), representing 13 existing faculties. This study uses a quantitative method with a sampling technique employing random sampling. The data collection technique utilized is scale distribution. The variable of public speaking anxiety uses a scale from Bartholomay & Houlihan (2016), which consists of 17 items. The self-efficacy variable uses the scale of Ralf Schwarzer and his colleagues (in Zhou, 2015), which consists of 10 items, and the emotional intelligence variable uses the scale of Schutte et al. (in Jonker & Vosloo, 2008), which consists of 29 items. The results of the study prove that: 1) Self-efficacy independently can be a predictor for the emergence of public speaking anxiety in UKSW students; 2) Emotional intelligence independently cannot play a role as a predictor for the emergence of public speaking anxiety in UKSW students; and 3) Self-efficacy and emotional intelligence together can play a role as a predictor, accounting for 12.7% of the appearance of public speaking anxiety in UKSW students.